The types of Ahodíus species described by Harold from Mexico with description of a new Genus (Coleoptera Scarabaeoidea: Ahodiidae) - Dellacasa, Marco; Gordon, Robert D.; Dellacasa, Giovanni (Instituto de Ecología, A.C., 1998)
In the present work, the tweive Mexican species of Aphodiini described by Haroid (azteca, flavocinctus, fuliginosus, grávidus, indutilis, lansbergei, luridiventris, mexicanas, oleosus, puncticeps, sallei and villosipes) are redescribed and illustrated with modern criteria based on the study of type material, leclotypes are aiso designated, The new genus Cephalocyclus is proposed for fuliginosus (type species), grávidus, luridiventris, mexicanus, puncticeps and villosipes. The taxonomía position of the remaining species-group taxa is aiso discussed in remarks.